Hubungan Hubungan Pengetahuan dan Persepsi Ibu Rumah Tangga terhadap Penggunaan Garam Beriodium di Wilayah Kerja Puskesmas I Tampaksiring: Pengetahuan dan Persepsi Ibu Rumah Tangga dengan Penggunaan Garam Beryodium: Studi Cross-sectional di Tampaksiring - Kadek Nuansa Putri Wulandari; Ni Ketut Sutiari (Amerta Nutrition, 2023)
Background: Iodine is an essential nutrient for the human body—lack of iodine in the body results in iodine deficiency disorders, which can cause various health problems. In Bali, Indonesia, 58% of the people use less iodized salt. The working area of Tampaksiring I Public Health Center alone has low iodized salt coverage of 44.9% of the target of 85% in 2019. Objectives: This study aimed to determine the correlation of knowledge and perceptions of housewives with the use of iodized salt at the Tampaksiring I Public Health Center. Methods: This cross-sectional study was conducted in April 2021, with 111 subjects obtained from calculations using accidental sampling. Meanwhile, the Chi-Square test was used in the analysis. Results: Of all research subjects, 59.5% of housewives are in the ‘good’ category for the knowledge of iodized salt; 51.4% have a good perception of iodized salt, and 70.3% have used iodized salt. Based on the analysis, no association is found between knowledge and use of iodized salt. However, this study reveals a relationship between perception and the use of iodized salt. Conclusions: Most housewives already have good knowledge and perception about iodized salt. Knowledge does not correlate with the use of iodized salt, while perception is related to the use of iodized salt. This is due to various factors such as habits, environmental factors, and the availability of iodized salt in the community.